Effects of injection timing on the engine performance and exhaust emissions of a dual-fuel diesel engine - SAYIN, CENK (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
In this study, influence of injection timing on the engine performance and exhaust emissions of a naturally aspirated, single cylinder diesel engine has been experimentally investigated when using ethanol blended diesel fuel from 0% to 15% with an increment of 5%. The engine load was selected as 15 and 30 Nm. The tests were conducted at five different injection timings (21 degrees, 24 degrees, 27 degrees, 30 degrees and 33 degrees CA BTDC) by changing the thickness of advance shim. The experimental test results showed that BSFC and emissions of NOx and CO2 increased as BTE and emissions of CO and HC decreased with increasing amount of ethanol in the fuel mixture. When compared to the results of original injection timing (27 degrees CA BTDC), NOx and CO2 emissions increased, and unburned HC and CO emissions decreased for the retarded injection timings (21 degrees and 24 degrees CA BTDC) at the all test conditions. On the other side, with the advanced injection timings (30 degrees and 33 degrees CA BTDC) decreasing HC and CO emissions diminished, and NOx and CO2 emissions boosted. in terms of BSFC and BTE, retarded and advanced injection timings compared to the original injection timing in the all fuel blends gave negative results for all engine speeds and loads. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Alternative fuel; Ethanol; Injection timing; Engine performance; Emissions; ETHANOL; COMBUSTION